XIAO: Tuning Code Clones at Hands of Engineers in Practice - Dang, Yingnong; Zhang, Dongmei; Ge, Song; Chu, Chengyun; Qiu, Yingjun; Xie, Tao (Annual Computer Security Applications Conference 2012, 2012)
During software development, engineers often reuse a code fragment via copy-and-paste with or without modifications or adaptations. Such practices lead to a number of the same or similar code fragments spreading within one or many large codebases. Detecting code clones has been shown to be useful towards security such as detection of similar security bugs and, more generally, quality improvement such as refactoring of code clones. A large number of academic research projects have been carried out on empirical studies or tool supports for detecting code clones. In this paper, we report our experiences of carrying out successful technology transfer of our new approach of code-clone detection, called XIAO. XIAO has been integrated into Microsoft Visual Studio 2012, to be benefiting a huge number of developers in industry. The main success factors of XIAO include its high tunability, scalability, compatibility, and explorability. Based on substantial industrial experiences, we present the XIAO approach with emphasis on these success factors of XIAO. We also present empirical results on applying XIAO on real scenarios within Microsoft for the tasks of security-bug detection and refactoring.